Solve by the linear combination method (with or without multiplication).

6x – 2y = 2
–3x + 4y = 5

1 answer

easiest way:
double the 2nd, then add that to the first
6y = 12
y = 2
sub back into the 1st
6x - 4 = 2
6x = 6
x = 1
Similar Questions
    1. answers icon 0 answers
    1. answers icon 1 answer
  1. Solve this system of linear equaiton by an algebraic method.So If I had to solve this the elimination method way, how would I do
    1. answers icon 3 answers
  2. What are the characteristics of a clickable interactive?(1 point) Responses Combination of linear and non-linear storytelling.
    1. answers icon 1 answer
more similar questions